THE ONE HEALTH APPROACH IN RABIES CONTROL THROUGH VACCINATION AND EDUCATION: A SYSTEMATIC REVIEW - Dewi Titis Angganingrum; Kadek Karang Agustina (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Rabies is one of the world's most fatal zoonotic diseases, with a case fatality rate of nearly 100% if post-exposure prophylaxis is not administered promptly. In Indonesia, rabies remains endemic in several regions, primarily transmitted through dog bites. The main challenges in its control include low animal vaccination coverage, limited public awareness, and suboptimal intersectoral coordination. This systematic review aims to analyze the effectiveness of the One Health approach in rabies control, specifically through vaccination and community education strategies. The Systematic Literature Review (SLR) method was employed by collecting and analyzing articles from databases such as Google Scholar, PubMed, and ScienceDirect published within the last 10 years. The One Health concept emphasizes integrated collaboration between the human health, animal health, and environmental sectors. The findings indicate that mass vaccination of rabies reservoir animals with a minimum of 70% annual coverage, combined with participatory, community-based education programs, significantly increases public knowledge and reduces transmission rates. Furthermore, the establishment of cross-sectoral coordination teams and community empowerment in health promotion efforts have proven effective in supporting sustainable rabies control. In conclusion, the One Health approach is a key strategy for achieving the global goal of eliminating dog-mediated human rabies by 2030, as outlined in the “Zero by 30” initiative.